Vaccination with the Staphylococcus aureus secreted proteins EapH1 and EapH2 impacts both S. aureus carriage and invasive disease. Issue 3 (14th January 2019) - Elshina, Elizaveta; Allen, Elizabeth R.; Flaxman, Amy; van Diemen, Pauline M.; Milicic, Anita; Rollier, Christine S.; Yamaguchi, Yuko; Wyllie, David H.
Highlights: We investigated the impact of vaccination with the S. aureus proteins EapH1 and EapH2. Intranasal vaccination with adenovirus expressing EapH1 and H2 reduced S. aureus carriage. EapH1/H2 vaccination also reduced bacterial load following i.v. injection of S. aureus. EapH1/H2 vaccination may offer an antibiotic-independent way of reducing S. aureus carriage. Abstract: Introduction: There is a need for an efficacious vaccine reducing infections due to Staphylococcus aureus, a common cause of community and hospital infection. Infecting organisms originate from S. aureus populations colonising the nares and bowel. Antimicrobials are widely used to transiently reduce S. aureus colonisation prior to surgery, a practice which is selecting for resistant S. aureus isolates. S. aureus secretes multiple proteins, including the protease inhibitors extracellular adhesion protein homologue 1 and 2 (EapH1 and EapH2). Methods: Mice were vaccinated intramuscularly or intranasally with Adenovirus serotype 5 and Modified Vaccinia Ankara viral vectors expressing EapH1 and EapH2 proteins, or with control viruses. Using murine S. aureus colonisation models, we monitored S. aureus colonisation by sequential stool sampling. Monitoring of S. aureus invasive disease after intravenous challenge was performed using bacterial load and abscess numbers in the kidney. Results: Intramuscular vaccination with Adenovirus serotype 5 and Modified Vaccinia Ankara viral vectors expressing EapH1 and EapH2 proteins significantly reduces bacterial recovery in the murine renal abscess model of infection, but the magnitude of the effect is small. A single intranasal vaccination with an adenoviral vaccine expressing these proteins reduced S. aureus gastrointestinal (GI) tract colonisation. Conclusion: Vaccination against EapH1 / EapH2 proteins may offer an antibiotic independent way to reduce S. aureus colonisation, as well as contributing to protection against S. aureus invasive disease.